A Study on the Visual Perception of Cultural Value Characteristics of Traditional Southern Fujian Architecture Based on Eye Tracking - Jianxun Deng; Junlong Chen; Ying Lei (Buildings)
The traditional Southern Fujian architecture serves as a reflection of the region’s deeply rooted cultural values. However, research on the architectural and cultural heritage of Southern Fujian remains scarce. Accordingly, this study employs eye-tracking technology to experiment with 20 individuals with local cultural backgrounds and 20 without it to investigate the differences in the perception of the architectural heritage of Southern Fujian by individuals with disparate cultural backgrounds. The findings indicate that distinct groups evince disparate visual perceptions of the architectural and cultural heritage of Southern Fujian. The participants’ attention was divided into two categories: patterns and shapes and calligraphy and text. Non-locals were primarily drawn to patterns and shapes, whereas locals demonstrated a greater interest in the calligraphy and text category. The extraction of cultural information from calligraphic characters requires greater understanding and more time spent within the culture. Knowledge of local cultural backgrounds is helpful to better understand such information. This highlights the potential impact of Southern Fujian architecture on the local population. These findings provide a compelling rationale for the incorporation of multicultural elements in contemporary architectural design while also advocating for the preservation and advancement of Southern Fujian architectural heritage.